Would We Be Able to Absorb the New Normal Brought by COVID-19 as Another Educational Revolution? - Seke, Mboungo Mouyabi (International Journal of Advanced Corporate Learning (iJAC), 2020)
There is no doubt that the present atmosphere has been no picnic for educational establishments, causing it almost difficult to keep on to work while holding fast to social removing and guaranteeing the security of students or learners and staff. This paper advocates the new ordinary as one of the key triggers of the new educational revolution. It contends that the Covid-19 crisis has compelled education foundations to rethink their model for passing on education in a worldwide society where mobility or movements of individuals are sincerely under peril. Past this contention, its discoveries explain the hidden variables of an educational revolution since the declaration of the second educational revolution 10 years prior. This investigation has furthermore worried on why leaders of education systems and organisations should absorb the new ordinary, aftereffect of the overall pandemic particularly, thinking about the extent of point of reference occasions to date. The author along these lines thinks the new typical will compel people to re-examine as the dangers control decisions have driven a colossal number of learners into brief "self-educating" conditions and others related circumstances, which have included the reason dispute of this paper.